Complete chloroplast genome sequence of Acacia crassicarpa (Fabaceae). Issue 8 (3rd August 2021) - Yue, Xinjian; Yu, Yuyun; Gao, Wei; Chen, Shipin; Weng, Zebin; Ye, Gongfu
Abstract: Acacia crassicarpa (Fabaceae), a nitrogen-fixing tree species, is critically important for coastal protection in southeast China. In this study, we report the complete chloroplast genome sequence of A. crassicarpa, with a length of 176, 493 bp. It contains a pair of inverted repeats (IR 39, 851 bp), a large single-copy region (LSC 91, 869 bp), and a small single-copy region (SSC 4, 922 bp). The complete genome comprises 138 genes, including 93 protein-coding genes, 37 tRNA, and 8 rRNA genes. Our phylogenetic analysis reveals that A. crassicarpa is closely related to A. podalyriifolia and A. dealbata .